Behavior modification of video gamers through cognitive behavioral therapy - Cheng, David Alexander K. (College of Education, University of the Philippines Diliman, 2019)
The purpose of the study was to evaluate the effectiveness of Cognitive-Behavior Therapy (CBT) on decreasing the problematic behaviors of participants. Using a quantitative-qualitative research design, 10 videogamers whose age ranged from 12 - 18 years old, and who showed characteristics consistent with internet gaming disorder participated in the study and have undergone a counseling intervention. The videogamers were assessed before and after exposure to Cognitive Behavior Therapy using IGDS-SF9, a nine-item short form scale to assess symptoms of internet gaming disorder. Results showed that cognitive behavior therapy is effective in decreasing the problematic behaviors of videogame addict. Hence, the said intervention is effective in addressing internet gaming disorder and it is seen to be a promising counseling framework compatible with the issues and concerns of individuals with videogame addiction. Finally, implications for counseling practice and educational landscape are discussed.